2019
DOI: 10.1111/iwj.13118
|View full text |Cite
|
Sign up to set email alerts
|

The use of povidone‐iodine and sugar solution in surgical wound dehiscence in the head and neck following radio‐chemotherapy

Abstract: Povidone‐iodine is known for successfully treating surgical wounds; the combination between povidone‐iodine and sugar, also called Knutson's formula, has been proposed to improve wound healing. Currently, no studies have investigated the effects of Knutson's formula to treat defects in wound closure following radio‐chemotherapy in the head and neck region. The aim of this study is to evaluate the efficacy of Knutson's formula in improving the wound‐healing process in patients who underwent radio‐chemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(26 reference statements)
0
6
0
Order By: Relevance
“… Caesarean section wound 10% PV-I solution (n=590) 4% chlorhexidine gluconate solution (n=524) 14 Karuserci et al (2019) 26 Turkey A prospective, randomized, controlled study PI: 33.92±11.09 Non-PI: 36.26±11.33 To research the impact of irrigation with PV-I and subcutaneous rifampicin on incisional surgical site infection. Gynaecologic surgery wound Saline + 10% PV-I (n=100) Saline (n=100) 15 Di Stadio et al (2019) 27 Italy A case-control study 60–75 To determine whether Knutson’s solution, which combines PV-I and sugar, is effective at speeding up the healing of wounds in patients who had radio-chemotherapy administered after having surgery for head and neck cancer. Wound dehiscence on head and neck cancer post-operative PV-I + sugar (n=18) Traditional topical drugs (n=16) 16 Chen et al (2021) 33 China A Randomized controlled trial ≥ 18 To compare wet-to-dry PV-I dressings versus wet silver dressings for wound healing in pemphigus vulgaris patients Skin erosions covering 10–70% of the body surface area.…”
Section: Resultsmentioning
confidence: 99%
“… Caesarean section wound 10% PV-I solution (n=590) 4% chlorhexidine gluconate solution (n=524) 14 Karuserci et al (2019) 26 Turkey A prospective, randomized, controlled study PI: 33.92±11.09 Non-PI: 36.26±11.33 To research the impact of irrigation with PV-I and subcutaneous rifampicin on incisional surgical site infection. Gynaecologic surgery wound Saline + 10% PV-I (n=100) Saline (n=100) 15 Di Stadio et al (2019) 27 Italy A case-control study 60–75 To determine whether Knutson’s solution, which combines PV-I and sugar, is effective at speeding up the healing of wounds in patients who had radio-chemotherapy administered after having surgery for head and neck cancer. Wound dehiscence on head and neck cancer post-operative PV-I + sugar (n=18) Traditional topical drugs (n=16) 16 Chen et al (2021) 33 China A Randomized controlled trial ≥ 18 To compare wet-to-dry PV-I dressings versus wet silver dressings for wound healing in pemphigus vulgaris patients Skin erosions covering 10–70% of the body surface area.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that povidone–iodine sugar ointment (U-PASTA; Kowa Company, Ltd. Japan), which is widely used for incurable ulcers, activates keratinocytes and fibroblasts and promotes wound healing [ 10 ], and its effectiveness in improving wound healing has been proven in clinical surgical wounds [ 11 ]. Povidone–iodine sugar ointment, which consists of 70% sugar and 3% povidone–iodine, also called Knutson’s formula, has been proposed to improve wound healing due to a reduction in bacterial contamination, rapid debridement of eschar, probable nourishment of surface cells, filling of defects with granulation tissue, and covering of granulation tissue with epithelium [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Its sugar component has been reported to inhibit biofilm formation by suppressing glycocalyx production [ 11 , 12 ]. Since Knutson et al reported in 1981 that SPI was useful for the treatment of multiple wound types, SPI has been widely used for treating diabetic ulcers, burns, and surgical wounds [ 13 17 ]. Currently, the Japanese Society of Pressure Ulcers recommends topical SPI use for pressure ulcers with inflammation and infection [ 18 ].…”
Section: Introductionmentioning
confidence: 99%